INOVASI GURU DALAM MENINGKATKAN KREATIFITAS BERPIKIR ANAK DI ERA 4.0 - Musrizal, Musrizal; Azhar, Azhar (Al-Rabwah, 2024)
Creativity is a very important skill for facing the challenges of the digital era, which continues to develop rapidly. In this 4.0 era, the ability to think creatively becomes increasingly important when facing rapid and complex changes. In this context, the role of teachers becomes very crucial in helping develop children's creative thinking. Innovative teachers can create a learning environment that stimulates children's creativity, thereby helping develop the creative thinking skills needed in the 4.0 era. One of the teacher innovations that can increase children's creative thinking in the 4.0 era is the application of an active and collaborative learning approach. In this approach, teachers encourage students to actively participate in the learning process through discussions, collaborative projects, or problem-based assignments. In this way, children have the opportunity to develop their critical and creative thinking skills, as well as learn to work in teams and share ideas with others. Through this active and collaborative learning approach, teachers are not only sources of knowledge but also facilitators and guides in the learning process